Concentration of amoxycillin and clavulanate in lung compartments in adults without pulmonary infection. Issue 11 (November 1994) - Cook, P J; Andrews, J M; Woodcock, J; Wise, R; Honeybourne, D
Abstract : BACKGROUND–The efficacy of an antibiotic is usually predicted from serum levels and MIC90 values for likely pathogens, but in the lung tissue concentrations may be more informative. This study compares concentrations of amoxycillin and clavulanate in serum, epithelial lining fluid (ELF), alveolar macrophages, and bronchial mucosa in 15 adults. METHODS–Amoxycillin 500 mg and clavulanic acid 250 mg were given 1-2 hours before diagnostic bronchoscopy for haemoptysis or radiological abnormality. Mucosal biopsy samples were taken from macroscopically normal sites, alveolar macrophages harvested by lavage, and ELF volume derived from urea concentrations in bronchial lavage fluid and blood. Amoxycillin was assayed by inhibition of growth of Micrococcus lutea, and clavulanate (in serum, ELF, and bronchial mucosa) by inhibition of growth of Klebsiella pneumoniae; in macrophages clavulanate was measured by high performance liquid chromatography. RESULTS–The median concentrations in serum were 6.90 mg/l for amoxycillin and 5.25 mg/l for clavulanate. The median bronchial mucosal concentration of amoxycillin was 2.99 mg/l and of clavulanate was 1.65 mg/l; the median concentrations in ELF were 0.89 and 0.96 mg/l, and in macrophages 0 and 0.76 mg/l, respectively. In macrophages amoxycillin levels were undetectable in 10 of 14 subjects (71%); by contrast, only 6 of 14 subjects (43%) had no detectable clavulanate. CONCLUSIONS–Clavulanate levels exceeded quoted MIC90 values (around 0.25 mg/l) for Legionella pneumophila both in ELF and in macrophages. Amoxycillin-clavulanate may therefore have a clinical role in infections with Legionella pneumophila.